2017
DOI: 10.5539/elt.v10n9p131
|View full text |Cite
|
Sign up to set email alerts
|

Project Based - Content Language Integrated Learning (Clil) at Mathematics Department Universitas Lampung

Abstract: This article aims at exploring wether project based content language integrated learning (CLIL) has s significant effect on the oral capability of students of science department of the University of Lampung. The number of students invoved in this study was 88 students. Quantitative data was obtained from the value of students' English proficiency before and after CLIL model application. While the qualitative data was obtained from the output of language produced by students during the learning process took pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Through practice, the CLIL researchers have concluded that students need more opportunities to apply what they have learned and the language in the CLIL classroom (Evnitskaya, 2014;Dwyer & de Boer, 2015;Yufrizal & Huzairin, 2017). One commonality among these ndings is the focus on active approaches to learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through practice, the CLIL researchers have concluded that students need more opportunities to apply what they have learned and the language in the CLIL classroom (Evnitskaya, 2014;Dwyer & de Boer, 2015;Yufrizal & Huzairin, 2017). One commonality among these ndings is the focus on active approaches to learning.…”
Section: Literature Reviewmentioning
confidence: 99%